2015
DOI: 10.1038/cr.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of kri1l causes definitive hematopoiesis failure via PERK-dependent excessive autophagy induction

Abstract: Dysregulation of ribosome biogenesis causes human diseases, such as Diamond-Blackfan anemia, del (5q-) syndrome and bone marrow failure. However, the mechanisms of blood disorders in these diseases remain elusive. Through genetic mapping, molecular cloning and mechanism characterization of the zebrafish mutant cas002, we reveal a novel connection between ribosomal dysfunction and excessive autophagy in the regulation of hematopoietic stem/progenitor cells (HSPCs). cas002 carries a recessive lethal mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 82 publications
1
40
0
Order By: Relevance
“…The ER stress responsive genes promote the apoptosis or autophagy process. 46,47 Erastin can also induce ER stress and up-regulates ER stress responsive genes. 5,48,49 The eif2α-ATF4 branch is the major signalling pathway activated by ferroptotic reagents (Figure 1).…”
Section: Er In Ferroptosismentioning
confidence: 99%
“…The ER stress responsive genes promote the apoptosis or autophagy process. 46,47 Erastin can also induce ER stress and up-regulates ER stress responsive genes. 5,48,49 The eif2α-ATF4 branch is the major signalling pathway activated by ferroptotic reagents (Figure 1).…”
Section: Er In Ferroptosismentioning
confidence: 99%
“…Mutants with CHT-specific hematopoietic defects include rumba (deficient in a C2H2 zing finger factor of unknown function) and samba (deficient in a homolog of human augmin complex subunit 3, HAUS3), which show a decrease in HSC number during the early CHT phase and the later expansion phase respectively (Du et al, 2011). A forward genetic screen for definitive hematopoietic mutations performed by Liu and colleagues has identified heterochronic mutants such as kri1l with low numbers of HSPCs in the CHT at days 3 and 5, whereas AGM hematopoiesis was not impaired (Jia et al, 2015). Species-specific hematopoietic differences in models of c-myb deficiency, further highlight the advantage of the zebrafish system.…”
Section: Introductionmentioning
confidence: 99%
“…The recent article in Cell Research published by Dr. Weijun Pan's group at the Institute of Health Sciences, Shanghai Institute for Biological Sciences, revealed that Kri1l, a previously undefined component of rRNA small subunit processome, is required for ribosome biogenesis and HSC development [5]. Their study was performed using zebrafish, which have emerged as a powerful model organism to model human development and disease [6].…”
mentioning
confidence: 98%
“…Moreover, the excessive PERK signaling appeared to be responsible for the defect in HSC emergence, since both pharmacologic inhibition of PERK and knocking PERK down using morpholinos, rescued HSC emergence in kri1l mutants. Thus, the defect in ribosome biogenesis in kri1l mutants appears to activate the PERK-EIF2 signaling axis, causing a marked increase in autophagy, which impairs HSC emergence and function and results in failure of definitive hematopoiesis [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation